2020
DOI: 10.1001/jamaoto.2019.3987
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Microvascular Retinal Signs and Age-Related Hearing Loss in the Atherosclerosis Risk in Communities Neurocognitive Study (ARIC-NCS)

Abstract: IMPORTANCE Given that age-related hearing loss is highly prevalent and treatable, understanding its causes may have implications for disease prevention.OBJECTIVE To investigate whether microvascular retinal signs are associated with age-related hearing loss attributable to a hypothesized underlying shared pathologic entity involving microvascular disease. DESIGN, SETTING, AND PARTICIPANTSThe Atherosclerosis Risk in Communities Neurocognitive Study (ARIC-NCS) is a community-based prospective cohort study of 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
5
2
Order By: Relevance
“… 15 More recently, Kim et al studied patients aged 45 to 64 and found that retinopathy was significantly associated with better rather than worse higher‐frequency hearing. 16 The difference in findings between our study and prior studies may be attributed to differences in the demographics of our cohort. Prior work has shown that the relationship between retinal pathology and hearing loss can be elucidated by examining the degree of microvascular pathology, with only those with more severe maculopathy or diabetic retinopathy being associated with worse hearing loss.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“… 15 More recently, Kim et al studied patients aged 45 to 64 and found that retinopathy was significantly associated with better rather than worse higher‐frequency hearing. 16 The difference in findings between our study and prior studies may be attributed to differences in the demographics of our cohort. Prior work has shown that the relationship between retinal pathology and hearing loss can be elucidated by examining the degree of microvascular pathology, with only those with more severe maculopathy or diabetic retinopathy being associated with worse hearing loss.…”
Section: Discussioncontrasting
confidence: 84%
“…They found an association between retinopathy and low‐frequency hearing loss in women only 15 . More recently, Kim et al studied patients aged 45 to 64 and found that retinopathy was significantly associated with better rather than worse higher‐frequency hearing 16 . The difference in findings between our study and prior studies may be attributed to differences in the demographics of our cohort.…”
Section: Discussioncontrasting
confidence: 81%
“…As such, retinal fundus photography is an important tool for translational vascular research. [366, 389, 384, 385, 378, 379, 394, 401, 367, 405, 390, 408, 368, 369, 398, 380, 365, 406, 370, 386, 395, 399, 403, 391, 412, 371, 387, 407, 372-374, 381, 375, 67, 402, 410, 404, 392, 400, 409, 393, 413, 376, 382, 377, 397] Microvascular health 6 [389,378,401,396,388,383] Analysis Vascular Plethysmography…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in disorders such as sickle cell disease and Susac syndrome, microvascular arterial disruption occurs through the "sickling" of red blood cells and endothelial cell disruption, respectively. Given that atherosclerosis [Kim et al, 2020], sickle cell disease [Strum et al, 2021], and Susac syndrome [Kleffner et al, 2016] are associated with hearing loss and vascular eye disease, it is likely that similar vascular processes occur in the ear and eye.…”
Section: Discussionmentioning
confidence: 99%